Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content: 1. National initiative for human development an innovative strategy to rehabilitate and develop human capital in Morocco Fatima Ghmimed, Jaouad El Bazoui, Abdelouahed Bouberria 2. The impact of the Companions on managing Hajj seasons and services in the first century of the Hijri era Shadia Abdul rahman Albalawi 3. The relationship between parental upbringing and divorce in Saudi Society Utilizing Case Study Approach: A case study in Jeddah province for a sample of divorced men and women Dr. Yahya Turki Al-Khazraj, Mohammed Ahmed Alghamdi 4. The Geographical Spread of The Corona Virus and The Economic Implications in Districts of Makka City Ms. Jalila Ali Hamad Jabri, Dr. Sami Salah Ghamry 5. Temporal and spatial analysis of air temperature change trends (thermal anomalies) in the Kingdom of Saudi Arabia during the period 1985-2016 AD Reem Mohammed Alshehri 6. Challenges of investing in heritage in the development plan in Morocco: The case of the Taza region – Morocco Younes El Azzouzi